SELLING CIGARETTES: THE EFFECTS OF SEXINESS LEVEL AND ETHNICITY OF SALES PROMOTION GIRL AMONG SMOKERS AND NON-SMOKERS - Fauzi, Hedi; Alif, Muhammad Gunawan (APPS Publications, 2019)
The aim of current study is to analyze the effects of cigarette sales promotion girl’s appearances as measured from sexiness level of uniform and ethnicity towards young smokers and non-smokers behavior and buying interest, which is represented through attitude towards the brand, and purchase intention. It was measured by nine different appearances of the cigarette sales promotion girl as the combination of sexiness level (casual, moderate, high) and ethnicity (Chinese descent, Native Indonesian and Western mix), and then it will be seen in influencing the attitude towards the model, attitude towards the brand, and purchase intention. As a quantitative research using experimental method between subjects designs, this study analyzes 507 subjects, divided into 278 young non-smokers and 229 young smokers. For non-smokers respondents, the sexiness level and ethnicity do affect the attitude toward the model but not the attitude towards the brand and purchase intention. Meanwhile, the result from the smoking respondents shows that the sexiness level and ethnicity do affect the attitude toward the model, attitude toward the brand and purchase intention. Moreover, young non-smokers give more positive response to the Western mix sales promotion girl wearing high level of sexy uniform, while young smokers give more positive response to the Native Indonesian and Western mix sales promotion girl wearing moderate level of sexy unform.